(untitled) (Bangladesh Journal of Pharmacology, 2013)
Cancer is a leading cause of death in the world. The rapid development of medicine and pharmacology allows to create new and effective anticancer drugs. Among modern anticancer drugs are bacterial proteins. Until now has been shown anticancer activity among others azurin and exotoxin A from Pseudomonas aeruginosa, Pep27anal2 from Streptococcus pneumoniae, diphtheria toxin from Corynebacterium diphtheriae, and recently discovered Entap from Enterococcus sp. The study presents the current data regarding the properties, action and anticancer activity of listed peptides.